Anti-Violence Persuasive Communication Patterns By “Sahabat Holic” Dangdut Lovers Community - Adiatma Pratama (Biokultur, 2021)
This study aims to describe the persuasive pattern of non-violent communication by the Sahabat Holic community as a pioneer of anti-violence dangdut lovers in their influence groups on the dangdut koplo music audience in Bantul. This research uses descriptive qualitative research methods. The research subjects were determined by purposive sampling technique, namely the community founder, community members, and dangdut koplo connoisseurs. The data validity technique in this study used the source triangulation technique. The data analysis technique in this research used interactive analysis methods which included data reduction, display data, and conclusion/verification. The results showed that persuasive communication against violence by the dangdut lover community Sahabat Holic used three communication patterns, namely 1) Human Communication, 2) Attempted Influence, and 3) Beliefs, Values or Attitudes.